Evaluation of left ventricular performance during supine exercise by transoesophageal M-mode echocardiography in normal subjects. Issue 1 (July 1982) - Matsumoto, M; Hanrath, P; Kremer, P; Tams, C; Langenstein, B A; Schlüter, M; Weiter, R; Bleifeld, W
Abstract : In order to evaluate left ventricular function during dynamic exercise transoesophageal M-mode recordings of the left ventricle were carried out with a newly developed transducer gastroscope system. Twelve healthy subjects performed a graded supine bicycle exercise test. Stable and good quality images of the left ventricle at rest and during exercise at different steps up to a maximum workload of 100 watts were obtained in all patients. Isotonic maximum exercise resulted in a significant increase in fractional shortening of the left ventricle, peak shortening rate, and peak lengthening rate of the left ventricular minor axis. Left ventricular end-diastolic dimension decreased significantly. With increasing workload the pressure rate product increased significantly. It is concluded that transoesophageal M-mode echocardiography is a useful method of evaluating left ventricular performance during dynamic exercise.